Harmonizing Digital Authentication Regulations: Legislative Framework for the Use of QR-Code in Notarial Practice - Irnanda, Firli; Deni, Fitra (Manunggal Halim Jaya, 2025)
The rapid development of information technology has significantly impacted notarial practices, particularly in the authentication of documents. One emerging innovation is the use of the Quick Response Code (QR code) as a verification tool and potential substitute for signatures on copies of notarial deeds. However, the current Indonesian legal framework does not explicitly regulate the legitimacy of QR-Codes within notarial procedures. This study aims to analyze the necessity of harmonizing Law No. 2 of 2014 on Notary Positions (UUJN) with Law No. 19 of 2016 on Electronic Information and Transactions (UU ITE) to accommodate digital authentication through QR-Codes. Using a normative juridical method combined with statutory, conceptual, and comparative approaches, this research examines the coherence of existing legal norms governing electronic signatures and notarial authority. The findings indicate that while QR-Codes offer advantages in terms of security, efficiency, and accuracy, the absence of explicit legal recognition creates uncertainty regarding the validity of digitally authenticated notarial documents. Therefore, regulatory harmonization through amendments to the UUJN and the issuance of implementing regulations is essential to establish legal certainty, security, and accountability in the use of QR-Codes. Such efforts are expected to promote a digital notarial system that is adaptive, transparent, and aligned with the principles of legal certainty in Indonesia.